b map evaluation and on-fault stress state for the Antakya 2023 earthquakes - V. Convertito; A. Tramelli; C. Godano (Scientific Reports, 2024)
Abstract The analysis of on-fault seismicity can enlighten the current stress state on the fault itself. Its definition is relevant to individuate fault patches that have not released all the accumulated stress even after the occurrence of a high magnitude earthquake. We use the b value to characterize the stress state on the fault of the Antakya 2023 main events, being b inversely proportional to the stress. The small magnitude seismicity occurring on the maximum slip fault-patches does not allow the b value estimation. This represents a strong indication that the maximum slip zone released most of the stress previously accumulated. Conversely, the lowest b values are located at the bends of the faults and close to the nucleation zone suggesting that, there, still exists not released stress implying that it could be reactivated in the future.